(untitled) (Heritage, 2024)
Extramarital union represents the union of life of one woman and one man who are not married. All modern family laws have accepted this form of community life, and in some European countries it is very widespread and precedes the conclusion of marriage. An extramarital union is a long-term union of the lives of two people, according to our legislation, which lacks the legal form of marriage. Another characteristic of cohabitation is its duration and stability. There is no single and universal interpretation of extramarital union in modern law. The differences are conditioned by the relationship of rights to the personal rights and obligations of partners in such a union. Some laws recognize the right to recognition of extramarital unions for persons of the same sex (Netherlands and France, Great Britain, Denmark), some require the registration of such unions (Belgium, France, Netherlands). The existence of the will of two persons to live in a union of life and the duration of the union are generally the minimum conditions for such an extramarital union to be legally recognized, i.e. to produce legal consequences. In some Western European countries, extramarital unions have become a common form of union between a man and a woman in the past few decades, but they are not legally regulated by the regulations of family legislation, as in Serbia, where the actions of such unions are regulated by regulations on the right to maintenance and the acquisition and division of joint property. Analysis of the application of family legislation to extramarital unions shows that due to certain unfavorable circumstances related to the birth of children out of wedlock, the protection of extramarital unions is not equal to the protection of married unions. Although protection is guaranteed to every family according to the Constitution, and the Family Law prescribes that children born in marriage are equal to children born out of wedlock in enjoying the rights and protection guaranteed to them by law, cohabitation does not enjoy nearly the same protection as the legislator intended for marriage . For example, the breakup of an extramarital union is not nearly as affected by the measures of the competent authorities as in the case of the termination of marriage. There is no conciliation procedure, there is no ex officio decision on entrusting children for care and upbringing, etc. Bearing in mind that extramarital union is a widespread form of community of life and that according to existing legislation it is not equal to married union in all aspects, the subject of consideration of this paper will be the causes of the origin and existence of extramarital union, its legal regulation from the aspect of international regulations and domestic legislation, the position and relations of partners in such a community with the aim of more efficient implementation of the constitutional framework according to which every family is guaranteed protection.